Daya Hambat Minyak Hati Ikan Hiu Terhadap Pertumbuhan Bakteri Porphyromonas gingivalis - Felisitas Maria Agustina; Dian Mulawarmanti; Yoifah Rizka Wedarti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2015)
Background: Porphyromonas gingivalis is the dominant bacteria that found in chronic periodontitis. Conventional antibacterial (antibiotic) especially tetracycline mostly used for periodontal treatment, but antibiotic ussage often causes resistant, allergy, and toxic. Shark Liver Oil Cenctrophorus sp species have antibacterial effect through its contents, squalene and squalamine that can be developed as an antibacterial adjuvant therapy in periodontal disease. Purpose: To examine the inhibition effect of Shark Liver Oil to the growth of Porphyromonas gingivalis. Materials and Methods: This study used a research design post test only control group design. The research subject is Porphyromonas gingivalis strain ATCC 33277 which have total amount 30 samples, divided into 5 groups. Three groups were given the shark liver oil with different concentrations of 10%, 15%, and 20%. Positive control were given the tetracycline and negative control were given the DMSO 1%. The inhibition was examined using diffution method and was inoculated on MH agar. The inhibitory effect has been observed by measuring the diameter of clear area on the disk using digital calipersin milimeter. Result: Shark liver oil could inhibit the growth of Porphyromonas gingivalis in every concentrations. Concentration 10% with 9,06 mm, concentration 15% with 11,31 mm, concentration 20% with 13,2 mm, while the negative control with 6,01 mm, and positive control with 30,09 mm. Conclusion: Shark liver oil could inhibit the growth of Porphyromonas gingivalis.